2002
DOI: 10.1637/0005-2086(2002)046[0886:seafto]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Effects and Fenbendazole Treatment of Turkey Ascaridiasis Under Simulated Field Conditions

Abstract: Under simulated natural conditions of bird production and parasite challenge, the effects of ascaridiasis and the effectiveness of fenbendazole treatment (6-day regimes in the feed at 16 ppm) were documented. Birds were artificially challenged with ascarid larvae on a daily basis from day 35 to 112, with bird grow out ending on day 119. Experimental groups, on a per pen basis, were infected control, treated with fenbendazole at days 63-69, treated with fenbendazole at days 63-69 and days 91-97, and uninfected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…A 90% reduction in a targeted worm population is the minimal level of activity a compound can exhibit for it to be considered efficacious [11,13]. Regardless of the parasite stage, fenbendazole was clearly shown to exhibit nematicidal activity greater than 90%, levels of efficacy that are consistent with previous reports [1,2,5,7]. The exact stage-specific percentages of worm reductions by levamisole are not so readily apparent, given its lack of efficacy and the extreme variance in worm populations both before and after treatment.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…A 90% reduction in a targeted worm population is the minimal level of activity a compound can exhibit for it to be considered efficacious [11,13]. Regardless of the parasite stage, fenbendazole was clearly shown to exhibit nematicidal activity greater than 90%, levels of efficacy that are consistent with previous reports [1,2,5,7]. The exact stage-specific percentages of worm reductions by levamisole are not so readily apparent, given its lack of efficacy and the extreme variance in worm populations both before and after treatment.…”
Section: Resultssupporting
confidence: 85%
“…These burdens are typically composed of several subpopulations of developmental stages [second-stage larvae (L2), third-stage larvae (L3), fourth-stage larvae (L4), and adults]. Infections are typically associated with lowered feed efficiency and lowered market weights [2,3]. With extreme in-fections, however, mortality may result [4].…”
mentioning
confidence: 99%
“…Several other parasiticides are used in the drinking water on a prescription ba-sis (levamisole, oxfendazole, and albendazole). Excellent efficacy has been documented for fenbendazole [2,3], nonefficacious activity has been cited for piperazine [4,5] and levamisole [6], and no documentation of efficacy has been reported for oxfendazole or albendazole in the turkey.…”
Section: Description Of Problemmentioning
confidence: 99%
“…However, another study indicated that ALB can be effective in protection of turkeys against Heterakis gallinarum or flagellated form of Histomonas (Hegngi et al , ). Clinical effectiveness in the treatment of turkeys infected by Ascaridia dissimilis is described for homologous drug fenbendazole (Yazwinski et al , ). Unfortunately, both ALB studies were performed without any knowledge of the pharmacokinetics of ALB and its active metabolite SOX.…”
Section: Introductionmentioning
confidence: 99%